Central Tendon Injury Impairs Regional Neuromuscular Activation of the Rectus Femoris Muscle - Yoshiaki Kubo (MDPI AG, 2021)
We aimed to uncover which rectus femoris strain injury types affect regional activation within the rectus femoris. The rectus femoris has a region-specific functional role; the proximal region of the rectus femoris contributes more than the middle and distal regions during hip flexion. Although a history of strain injury modifies the region-specific functional role within the rectus femoris, it was not obvious which rectus femoris strain injury types affect regional activation within it. We studied 12 soccer players with a history of rectus femoris strain injury. Injury data were obtained from a questionnaire survey and magnetic resonance imaging. To confirm the region-specific functional role of the rectus femoris, surface multichannel electromyographic signals were recorded. Accordingly, eight legs had a history of central tendon injury, four had a history of myofascial junction injury, and four had a healed strain injury. When the injury was limited to the central tendon, the region-specific functional role disappeared. The region-specific functional role was confirmed when the injury was outside the central part. The neuromuscular function was also inhibited when the longitudinal range of the injured region was long. Our findings suggest that a central tendon injury with a long injury length impairs regional neuromuscular activation of the rectus femoris muscle.